2013
DOI: 10.1007/s10681-013-0904-4
|View full text |Cite
|
Sign up to set email alerts
|

Breeding melon for resistance to Fusarium wilt: recent developments

Abstract: Melon Fusarium wilt (MFW), caused by Fusarium oxysporum f. sp. melonis (Fom), is one of the most destructive diseases of melon (Cucumis melo L.). The development and deployment of resistant cultivars is generally considered to be the best approach to control MFW. Based on the host resistance genes associated with variants of this pathogen, Fom isolates were classified into four physiological races designated 0, 1, 2, and 1,2. Two dominant resistance genes, Fom-1 and Fom-2, control resistance to races 0 and 2, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
29
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(29 citation statements)
references
References 80 publications
0
29
0
Order By: Relevance
“…Hans (F.o.m) causes muskmelon Fusarium wilt (MFW). The MFW decreases both fruit yield and quality apart forcing intensive use of chemical fungicide sprays (Gordon et al 1990, Oumouloud et al, 2013. The formation of perennating chlamydo spores in soil by this fungus and the ability to infect and colonize the root system of non-host plants and melon rotation crops equips it to sustain its population in soil over gap and crop cover other than melon (Gordon et al, 1989).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Hans (F.o.m) causes muskmelon Fusarium wilt (MFW). The MFW decreases both fruit yield and quality apart forcing intensive use of chemical fungicide sprays (Gordon et al 1990, Oumouloud et al, 2013. The formation of perennating chlamydo spores in soil by this fungus and the ability to infect and colonize the root system of non-host plants and melon rotation crops equips it to sustain its population in soil over gap and crop cover other than melon (Gordon et al, 1989).…”
Section: Introductionmentioning
confidence: 99%
“…The synthesis and amount of secondary metabolites i.e. phytoalexins, enzymes defending reactive oxygen species (ROS), and cell wall-building processes like necrosis, callose deposition and lignification in response to invasion by fungal pathogens play a vital role in imparting resistance to F.o.m infection (Oumouloud et al, 2013). The F.o.m.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Further analysis has shown that FOM-2 has two structural and functional domains, the nucleotide-binding (NB)-adaptor shared by APAF-1, R proteins, and CED-4 (ARC) and the LRR, which are present in typical R genes. Some markers have been developed in previous studies for the Fom-2 gene (Oumouloud et al, 2013); however, most of these molecular markers were designed for the thick-rind melon and are not useful for the Chinese thin-rind melon (oriental melon). In the present study, we developed a new molecular marker for melon wilt and verified it for both thick-and thin-rind melons.…”
Section: Introductionmentioning
confidence: 99%
“…The identification of Fom ‐ resistant traits represents a fundamental objective in melon breeding programmes. Efforts have been devoted to searching for natural sources of resistance, and in characterizing the molecular basis of melon resistance to Fom (Burger et al ., ; Perchepied & Pitrat, ; Álvarez et al ., ; Oumouloud et al ., , ). The use of molecular tools has contributed to a better characterization of the defensive response of melon accessions to Fom isolates (Oumouloud et al ., ; Haegi et al ., ).…”
Section: Introductionmentioning
confidence: 99%